Republic of Armenia : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses results of a technical assistance report prepared to evaluate the quality of Armenia's public investment institutions in the planning, budgeting, and implementation stages of public investment management. Significant gaps exist in the efficiency of public investments, both in terms of physical outputs and quality. The report also highlights that in a context of limited fiscal space, the scaling up of public investments will require the prioritization of efforts to introduce reforms in the following areas in need of urgent action. The recommendations in this report prioritize the eight actions at the key stages of the project cycle and for the Ministry of Finance's capacity development. Recommendation is also made to establish a constraint on in-year changes in project implementation plans and complete the transformation of the Audit Chamber from the Control Chamber. Armenia is expected to have a more robust audit function when the provisions in the new Law on the 'Audit Chamber' are fully implemented.